The Efficacy of Murottal and Prayer as Therapy for The Management of Elderly's Anxiety and Sleep Disturbances - Galih Noor Alivian; Sidik Awaludin; Arif Imam Hidayat; Iwan Purnawan (Jurnal Berita Ilmu Keperawatan, 2022)
Aging is a natural process characterised by predictable physical and behavioral alterations that all people experience as they progress through their lives. Anxiety and sleep disorders are two issues that plague the elderly. The elderly typically complain about sleeping issues as a result of various chronic diseases. Frequent night awakenings might lead to an increase in the amount of time spent sleeping during the day. The aim of this study was to see how efficient murottal and prayer are at reducing anxiety and sleep problems in the elderly. This study employs an experimental design with a before and post approach, as well as a control group. This study collect 60 samples from elderly people in Pamijen Village. They were split into two groups: 30 elderly in the murottal group and 30 elderly in the prayer group. A questionnaire was used to assess anxiety and sleep pattern disturbances before and after treatment. Simple random sampling was used as the sampling technique. The paired t-test was used to analyse the dataStatistical tests of differences in sleep patterns before and after treatment in the murottal and pray groups were p = 0.00, statistical tests of anxiety scores before and after listening to prayer were p = 0.869, and statistical tests of differences in sleep patterns before and after treatment in the murottal and pray groups were p = 0.00. Murottal therapy has been shown to be effective in reducing anxiety and sleep disturbances